The effectiveness of mindfulness-based therapy and positive thinking on emotion regulation and defense mechanisms in people with borderline personality disorder in improving post-traumatic brain injury - SeyedEbrahimi , Seyed AliAsghar (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: Today, the effects of positive thinking and mindfulness training on anyone are not hidden and its positive effects on patients can be seen. The aim of this study was to evaluate the effectiveness of mindfulness and positive thinking therapy based on emotion regulation and defense mechanisms in people with borderline personality disorder in improving post-traumatic brain injury by quasi-experimental method. Methods: The statistical population of this study was patients with borderline personality disorder due to traumatic brain injury, from which 60 people were selected for this study by cluster random sampling. This study was performed based on pre-test and post-test with a control group (30 in the experimental group and 30 in the control group). The data collection tools in the present study were the standard Garnfsky Emotion Regulation Questionnaire (2001) and the Andrews Standard Questionnaire (1998). Descriptive statistics and analysis of covariance were used to analyze the data. Results: Based on the results obtained in the pre-test stage, there was no significant difference between the experimental and control groups in terms of emotion regulation level and defense mechanisms. But after the intervention (positive thinking training and mindfulness training) a significant difference was observed between the two groups. Conclusion: According to the modified means of analysis of covariance, it can be concluded that training positive thinking and mindfulness skills improves the level of emotion regulation and improves defense mechanisms in the experimental group compared to the control group.